Toughened one-component epoxy adhesives with improved humidity resistance
By using components such as barrier PU polymer enhancers and urea derivatives in a-component structural glue, the problem of insufficient moisture resistance of colloids in high humidity environments is solved, and the moisture resistance and dynamic performance of colloids are significantly improved.
Patent Information
- Application Number
- JP2024225881
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-06-18
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-23
AI Technical Summary
When used in high humidity environments, the existing component structural glue lacks sufficient moisture resistance, resulting in a decrease in colloid hardening performance and increased strength loss. The bubbles precipitated by water vapor in an electroplating oven may lead to the destruction of the colloid layer.
A-component structural adhesive is used that includes a barrier PU polymer reinforcement, solid or liquid epoxy resin, hardener, urea derivative and optional filler. Among them, the barrier PU polymer reinforcement is composed of polyethanol ether, hydroxide terminal butadiene, polyisocyanic acid, chain extension agent and capping group.
It significantly improves the moisture resistance and dynamic performance of the colloid, and enhances the overall moisture resistance and performance stability of the colloid.
Smart Images

Figure 2025066698000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a one-part epoxy adhesive composition that exhibits improved moisture resistance. The epoxy adhesive composition comprises a blocked PU polymer toughening agent compound, an epoxy resin compound, and The blocked PU polymer toughener contains a hardener and a urea compound. of a reaction mixture comprising an xyl-terminated polybutadiene, a polyisocyanate and a capping group. It is a reaction product. [Background technology]
[0002] Structural epoxy one-component body shop adhesives are widely used in automotive manufacturing. In the automotive industry, for some joining applications, adhesives that can withstand high humidity environmental conditions in the uncured state are used. Adhesives must be optimized for this purpose. Insufficient moisture resistance can lead to the formation of The strength performance of the adhesive may be compromised (i.e. greater strength loss), and / or or its failure mode to the substrate may be compromised (i.e. lower cohesive failure and Higher adhesive failure, caused by outgassing of water while curing the adhesive in an electrocoat oven There are many common manufacturing situations where the adhesive is exposed to high humidity conditions for extended periods before curing. do.
[0003] For example, in the pre-series molds of new car models, adhesive is applied to the body structure and the The vehicle is not immediately subjected to the electroplating process, but rather to the assembly of the glazing panels. It may be left for a long time before heat treatment, so the adhesive remains uncured. The coating is then exposed to external moisture and temperature conditions in an electrodeposition oven until cured.
[0004] Another common manufacturing practice in the automotive industry is to manufacture parts in one country or region and Then export and / or ship to another location (e.g., country or region) for final assembly. This is called CKD (Complete Knockdown). The entire body is formed in place and assembled before undergoing an electro-deposition process in which the adhesive hardens. The equipment is then transported to another location for erection. Summary of the Invention [Problem to be solved by the invention]
[0005] In many countries, manufacturing sites have discontinuous work cycles, e.g. holidays. Before the holiday, the vehicle or part that was formed may not be subjected to the entire electro-deposition process. The line may be shut down for a holiday and then the vehicle or part may be electroplated after production resumes. undergo the process.
[0006] These and other one-part epoxy adhesives have a long time between application and cure. In manufacturing situations, it is desirable to have an adhesive technology where the bulk adhesive exhibits increased moisture resistance. It would be interesting. [Means for solving the problem]
[0007] The present invention comprises: A) a blocked PU polymer toughening compound; B) a solid epoxy resin; C) a liquid an epoxy resin component comprising an epoxy resin or a mixture thereof; C) a hardener; D) a urea compound; preferably phenyl dimethyl urea or aliphatic dimethyl urea; and E) optionally, Fillers, preferably fumed silica, calcium carbonate, calcium oxide, wollastonite One-component structural adhesive containing one or more of the following: carbide, talc, glass beads, and hollow glass spheres. The blocked PU polymer toughening agent (A) is i) a polyether, preferably a polytetrafluoroethylene (PTFE) copolymer. ii) hydrofluoric acid polymer; iii) hydroxyl-terminated polybutadiene; an isocyanate, preferably 1,6-hexamethylene diisocyanate; iv) a chain extender , preferably bisphenol, and v) a capping group, preferably cashew nut shell liquid. It is a one-part structural adhesive that is the reaction product of a reactive mixture that includes an oil.
[0008] In one embodiment of the present invention, the one-part structural adhesive described hereinabove has the formula: [ka] The epoxy resin (B) has the formula:
[0009] In one embodiment of the present invention, the one-part structural adhesive described hereinabove Component A) is present in an amount of 5 to 25 weight percent; component B) is present in an amount of 1 to 60 weight percent. component C) is present in an amount of 1 to 8 weight percent; component D) is present in an amount of 0. and component E) is present in an amount of 0 to 30 weight percent. The weight percentages are based on the total weight of the one-part structural adhesive.
[0010] In one embodiment of the present invention, the one-part structural adhesive described hereinabove The reaction mixture of component A) comprises: i) 10 to 95 weight percent polyether; ii) 2 to 10 weight percent olefin copolymer; 60 weight percent hydroxyl-terminated polybutadiene; iii) 2 to 40 weight percent iv) 0 to 20 weight percent of a chain extender, and v) 0.1 to 20 weight percent of a polyisocyanate. 50 weight percent of the capping group, the weight percent being based on the total weight of the reaction mixture. This serves as the standard. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a photograph of the 10% lap shear failure exhibited by Example 12. [Diagram 2] FIG. 2 is a photograph of the 40% lap shear failure exhibited by Example 6. [Diagram 3] FIG. 3 is a photograph of the 100% lap shear failure exhibited by Example 20. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] It is to be understood that specific details set forth herein are presented for purposes of illustration and are not intended to be limiting of the scope of the invention. For purposes of discussion only, the invention is presented in a manner that is most useful and easily understood in terms of the principles and conceptual aspects of the invention. The present invention is presented to provide what is believed to be an illustrative example. No attempt is made to describe the invention in more detail than is necessary for an understanding of the invention, and this description The following description will make clear to one skilled in the art how several aspects of the invention may be embodied in practice.
[0013] Unless otherwise stated, a reference to a compound or component includes the compound or component itself and the compound itself. The present invention also includes combinations of other compounds or components such as a mixture of
[0014] As used herein, the singular forms "a," "an," and "the" are used interchangeably. Unless the context clearly dictates otherwise, plural referents are included.
[0015] Unless otherwise indicated, the amounts of ingredients used in this specification and claims are All numbers expressing conditions, etc. are in all cases modified by the term "about." Therefore, unless otherwise indicated, the remainder of this specification The numerical parameters set forth in the specification and appended claims are to be obtained by the present invention. is an approximation that may vary depending on the desired properties sought. They should not be construed as an attempt to limit the scope of the claims, and each numerical parameter should be recited with respect to the number of significant digits. It should be interpreted in terms of the number of digits and normal rounding practices.
[0016] Moreover, the recitation of numerical ranges within this specification is a disclosure of all numerical values and ranges within that range. For example, if the range is 1 to 50, then 1, 7, 34, 46.1, 23.7 or any other value or range therein. When a meter, variable or other quantity is stated with a set of upper and a set of lower limits, This shall be understood as an explicit disclosure of all ranges formed by each pair of upper and lower limits. It should be.
[0017] The present invention is an enhanced one-part epoxy adhesive composition that exhibits improved moisture resistance. The one-part structural adhesive of the present invention comprises: A) a blocked PU polymer toughening compound; B) a solid ethylene glycol (EDTA) copolymer; C) an epoxy resin component comprising an epoxy resin, a liquid epoxy resin or a mixture thereof; C) a hardener D) a urea compound; and E) optionally, comprising or consisting essentially of a filler, The blocked PU polymer toughening agent (A) is composed of i) polyether, ii) hydride, iii) a polyisocyanate; iv) a chain extender; and v) Reaction products of reaction mixtures comprising, consisting essentially of, and consisting of capping groups. It is an object.
[0018] Surprisingly, the present inventors have discovered that one-part epoxy adhesive compositions, and in particular their toughener components, Increasing the overall hydrophobicity of the cured one-part epoxy adhesive greatly improves the moisture resistance The inventors have found that this results in improved dynamic properties of the composition. This improvement can be achieved by designing reinforcements with specific building blocks as disclosed in In addition, the composition and amount of the curing accelerator play an important role.
[0019] Enhanced one-part epoxy adhesives are used for joining metal to metal and metal to other materials. These adhesives are often used in the automotive and other industries to The adhesive contains a "reinforcement agent" that makes the adhesive less susceptible to breakage. The reinforcement agent is a substance that breaks off under the conditions of the curing reaction. Blocked hydroxyl groups of epoxy resins, such as DER331 This type has a blocked isocyanate group that allows it to react with the isocyanate group. The reinforcing agents are described, for example, in U.S. Pat. Nos. 5,202,390 and 5,278,257. No. 2005 / 118734, WO 2007 / 0036 No. 50, No. 2012 / 091842, U.S. Patent Application Publication No. Specification No. 2005 / 0070634, Specification No. 2005 / 0209401, No. 20 EP-A-0308664, EP-A-06 / 0276601, Specification No. 1498441A, Specification No. A-1728825, Specification No. A-1896517 No. A-1916269, No. A-1916270, No. A This is described in specifications A-1916272 and A-1916285.
[0020] The toughening agent is an elastomeric material having end-capped isocyanate groups. The toughening agent is preferably a blocked PU polymer toughening agent compound (A). The mixture of isocyanate-terminated compounds is chain extended, and the remaining isocyanate groups of the chain extended material are then converted to isocyanate groups. It is manufactured by a process that includes a capping step.
[0021] The isocyanate-terminated compound is (i) a small amount of a compound having a number average molecular weight of 1,000 to 10,000. at least one isocyanate-terminated polyether, and (ii) 1,000 to 10,000 The composition comprises at least one isocyanate-terminated diene polymer having a number average molecular weight of 0.
[0022] The polyether portion of the isocyanate-terminated polyether is Lamethylene oxide) (sometimes called polytetrahydrofuran diol polymer) ), 1,2-butylene oxide, 2,3-butylene oxide, 1,2-propylene oxide The total weight of the polymer or copolymer may be one or more polymers of ethylene oxide and ethylene oxide. At least 70% by weight of tetrahydrofuran, 1,2-butylene oxide , 2,3-butylene oxide and 1,2-propylene oxide. At least 80% by weight, based on the total weight of the polymer or copolymer, Polymers of tetrahydrofuran are particularly preferred.
[0023] Isocyanate-terminated polyethers are prepared by reacting amine and / or hydride groups on the starting polyether. At least 1.5 equivalents, preferably 1.8 to 2.5 equivalents or 1. Amine-terminated or hydroxyl-terminated polyethers are added to polyisocyanates in a ratio of 9 to 2.2 equivalents. The starting polyether is preferably one molecule Each of the polyamines has 2 to 3, and more preferably 2, amine and / or hydroxyl groups. The reisocyanate preferably has two isocyanate groups per molecule. The cyanate-terminated polyether preferably has 2 to 3 units per molecule, more preferably 2 The starting polyether preferably has a molecular weight of 900 to 8000 and More preferably, it has a number average molecular weight of 1,500 to 6,000 or 1,500 to 4,000. The polyisocyanate preferably has a molecular weight of up to 300.
[0024] The isocyanate-terminated diene polymer may be prepared by reacting an amine group and / or an isocyanate-terminated diene polymer with an amine group and / or an isocyanate-terminated diene polymer. At least 1.5 equivalents per equivalent of hydroxyl group, or 1.8 to 2.5 equivalents, or 1. Amine-terminated or hydroxyl-terminated diene polymers are added to polyisocyanates in a ratio of 9 to 2.2 equivalents. It is conveniently prepared by reacting with an aryl ester.
[0025] The starting diene polymer is preferably cooled to -20°C or below prior to reaction with the polyisocyanate. , preferably having a glass transition temperature of -40°C or less. The diene polymer preferably has The conjugated diene is preferably butadiene or isoprene. Among these, butadiene is particularly preferred.
[0026] The starting diene polymer preferably has 2 to 3, more preferably 2, per molecule. The polyisocyanate preferably has one molecule The isocyanate-terminated diene polymers are preferred. Preferably, one molecule has 2 to 3, more preferably 2, isocyanate groups. The ethylene polymer preferably has a molecular weight of 900 to 8000, more preferably 1,500 to 6,000. The polyisocyanate has a number average molecular weight of 0, and more preferably 2,000 to 3,000. The nate preferably has a molecular weight of up to 300.
[0027] The isocyanate-terminated polyethers and isocyanate-terminated diene polymers are aromatic Although it may have isocyanate groups, the isocyanate groups are preferably aliphatic. When an isocyanate-terminated polymer is produced by the above method, the polyisocyanate is an aromatic It may be a polyisocyanate, but it is preferably isophorone diisocyanate, 1,6-Hexamethylene diisocyanate, Hydrogenated toluene diisocyanate, Hydrogenated meth Ethylenediphenylisocyanate (H 12 MDI) etc. be.
[0028] The isocyanate-terminated polyether and the isocyanate-terminated diene polymer are separately Alternatively, they may be prepared as described above and then blended. Amine or hydroxyl terminated polyethers and amine or hydroxyl terminated diene polymers and reacting the blended material with a polyisocyanate to form an isocyanate. They are produced simultaneously by forming a mixture of the end species directly.
[0029] The weight ratio of the isocyanate-terminated polyether to the isocyanate-terminated diene polymer is For example, the weight ratio may be 5:95 to 95:5. A preferred weight ratio is 50:50 to 95:5, more preferably A more preferable ratio is 70:30 to 90:10.
[0030] The reaction to form the isocyanate-terminated polymer may optionally be carried out with an isocyanate A catalyst for reacting the isocyanate groups with the isocyanate-reactive groups of a polyether or diene polymer. In the presence of a solvent, the materials are mixed in the above ratio and heated to 60-120°C. Until the isocyanate content is reduced to a constant or target value or The amine and / or hydroxyl groups of the starting polyether or diene polymer are eliminated. The reaction is continued until consumed.
[0031] Optionally, isocyanate-terminated polyether and / or isocyanate-terminated diene Branches can be introduced into the polymers by the process described above. When produced, this is divided into the reaction between the polymeric starting material and the polyisocyanate. This can be achieved by adding a branching agent. For the purposes of this invention, the branching agent is 9, preferably 50 to 500, and at least three hydroxyl groups per molecule. Polyol or polyamine compounds having silyl, primary amino and / or secondary amino groups If used at all, the branching agent generally comprises a copolymer of the branching agent and the starting polypolymer (or i.e., amine-terminated or hydroxyl-terminated polyether or diene polymers) by weight. It constitutes no more than 10%, preferably no more than 5%, and even more preferably no more than 2%. Examples of the polyol include trimethylolpropane, glycerin, and trimethylol ether. Tan, ethylene glycol, diethylene glycol, propylene glycol, dipropylene Glycol, sucrose, sorbitol, pentaerythritol, triethanolamine amine, diethanolamine, etc., as well as amines having a number average molecular weight of up to 599, especially up to 500 Examples of such alkoxylates include those alkoxylates.
[0032] A mixture of isocyanate-terminated polyether and isocyanate-terminated diene polymer is , which is chain extended to produce a chain extended isocyanate terminated prepolymer. The agent is a polyol or polyamine having a molecular weight of up to 749, preferably 50-500. Compounds and two hydroxyl, primary amino and / or secondary amino groups per molecule Examples of suitable chain extenders include aliphatic diols, such as ethylene glycol, diols, Ethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol Recall: Tripropylene glycol, 1,4-butanediol, 1,6-hexanediol aliphatic or aromatic diamines, such as ethylene diamine, cyclohexane dimethanol, etc. Amines, piperazine, aminoethylpiperazine, phenylenediamine, diethyltoluene diamines, etc., as well as compounds with two phenolic hydroxyl groups, e.g. resorcinol ol, catechol, hydroquinone, bisphenol, bisphenol A, bisphenol AP (1,1-bis(4-hydroxyphenyl)-1-phenylethane), Nol F, bisphenol K, bisphenol M, tetramethylbiphenol and o,o '-Diallyl-bisphenol A. In particular, two phenol hydrochlorides Compounds having xyl groups are preferred. A preferred polyol is a hydroxy-terminated butadiene polyol. It may be a homopolymer or a copolymer such as polybutadiene diol.
[0033] The chain extension reaction is carried out in the same general manner as the prepolymer formation reaction. By mixing the polymer with a chain extender, one of the isocyanate-reactive groups contributed by the chain extender is At least two equivalents of isocyanate groups are obtained per unit amount of the chain extender. 1.5 to 4 or more, preferably 1.75 to 3 per equivalent of the isocyanate reactive group More preferably, 1.8 to 2.5 equivalents of isocyanate groups can be obtained.
[0034] The chain extension reaction is carried out by reacting an isocyanate-terminated polyether with an isocyanate-terminated diene polymer. The mixture is mixed with a chain extender, and the isocyanate-reactive groups of the chain extender are reacted with the isocyanate. Mix under conditions that react with the isocyanate groups of the terminal material to form a chain-extended prepolymer. This is done by offering something.
[0035] The chain extended prepolymer becomes a mixture of materials, mainly consisting of residues of the chain extender. isocyanate-terminated polymers corresponding to two or more starting isocyanate-terminated polymers bonded together by In one embodiment, a portion of the prepolymer molecules is composed of isocyanate-terminated polymers. The polyether chains of the ester-terminated polyether are two or more. In another embodiment, a portion of the prepolymer molecules are polyether polyethers of isocyanate terminated polyethers. One or more polyether chains corresponding to the polyether chains and an isocyanate-terminated diene polymer The isocyanate has one or more diene polymer chains corresponding to the diene polymer chain of the isocyanate. It has two further diene polymer chains corresponding to the diene polymer chains of the terminal diene polymer. The chain-extended prepolymer may contain small amounts of unreacted starting material. and / or one molecule of chain extender and one molecule of isocyanate-terminated polyether or may contain small amounts of reaction products with isocyanate-terminated diene polymers.
[0036] The chain extension reaction conditions are usually determined by mixing an amine or hydroxyl terminated polymer with a polyisocyanate. The reaction is as described for the reaction with acetone.
[0037] The isocyanate groups of the chain-extended prepolymer are then reacted with a capping group. No. 5,200,633, all of which are incorporated herein by reference. Specification No. 2,390, Specification No. 5,278,257, Specification No. 7,615,595 U.S. Patent Application Publication Nos. 2005-0070634 and 2005-02094 No. 01, No. 2006-0276601 and No. 2010-001953 9, WO 2006 / 128722, WO 2005 / 118 734 and 2005 / 0070634 Various types of capping groups are suitable, including those
[0038] Among the useful capping agents are the following: a) Aliphatic, aromatic, alicyclic, arylaliphatic, having one primary or secondary amino group Examples of such capping compounds include aromatic and / or heteroaromatic monoamines. ethylamine, ethylamine, isopropylamine, sec-butylamine, t-butylamine Monoalkylamines such as dimethylamine, diethylamine, diisopropylamine, etc. Dialkylamines such as dihexylamine, di-sec-butylamine, dihexylamine and dioctylamine cyclohexylamines, in which the cyclohexyl group may be optionally substituted with one or more alkyl groups; Hexylamine or dicyclohexylamine; any alkyl group having one or more phenyl groups Selectively substituted benzylamines and diphenylamines; morpholine; amine hydrogen atoms Examples of such alkyl groups include N-alkyl piperazines and imidazoles having alkyl groups. b) Phenolic compounds such as monophenols, polyphenols and aminophenols. Examples of monophenols include phenol, 1-phenylenediamine ... Alkylphenols containing one or more alkyl groups, naphthols, halogenated phenols, Preferred alkylphenols include cardanol and naphthol. The polyphenols in question are cashew nut shell liquid (CNSL), sometimes called , containing two or more, preferably two, phenolic hydroxyl groups per molecule, Cinol, catechol, hydroquinone, bisphenol, bisphenol A, bisphenol AP (1,1-bis(4-hydroxyphenyl)-1-phenylethane), Bisphenol Bisphenol F, bisphenol K, bisphenol M, tetramethylbiphenol and o, o'-Diallyl-bisphenol A and its halogenated derivatives are preferred. Suitable aminophenols have at least one primary or secondary amino group and one phenol group. The amino group is preferably a carbon atom of an aromatic ring. Examples of suitable aminophenols are 2-aminophenol, 4-aminophenol, Among the phenolic compounds, Monophenols and aminophenols are generally preferred. c) benzyl alcohol, which may be substituted on the aromatic ring with one or more alkyl groups; d) 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4- Hydroxybutyl acrylate, 2-hydroxybutyl acrylate, 2-aminopropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate acrylate, 4-hydroxybutyl methacrylate and 2-hydroxybutyl methacrylate hydroxy-functional acrylate or methacrylate compounds such as acrylates; e) Dodecanethiol, etc., alkyl groups having 2 to 30, preferably 6 to 16 carbon atoms. thiol compounds such as alkylthiols having an atom; f) acetamides and N-alkylacetamides having at least one amine hydrogen Alkylamide compounds having the formula: g) Ketoximes.
[0039] Monophenol and polyphenol capping agents are generally preferred. In the form, at least 90% of the isocyanate groups of the prepolymer are 95%, more preferably at least 98%, and up to 100% are one or more of these types In such an embodiment, any remaining capping agent may be present. The uncapped isocyanate groups are also capped with another type of capping agent. It is possible.
[0040] The capping reaction optionally involves capping an isocyanate group with the isocyanate of a capping agent. The reaction is carried out under the general conditions already described in the presence of a catalyst for reacting with the ester-reactive group. Under the conditions described above, mix the ingredients in the ratios listed and react them at room temperature or at high temperatures such as 60 to 120°C. This can be carried out by reacting the isocyanate at a constant value (this is the preferred The reaction is continued until the isocyanate groups are reduced to 0.1% by weight. Less than 3%, preferably less than 1%, of the capped pores may remain uncapped.
[0041] The obtained toughener was analyzed by GPC, considering only the peaks representing molecular weights above 1,000. It is preferably at least 3,000, preferably at least 4,000 to about 35,000, preferably up to about 25,000, more preferably up to about 20,000 It has an average molecular weight.
[0042] Particularly preferred prepolymers have an average of 1.9 to 2.2 capped ions per molecule. Contains a socyanate group.
[0043] The toughening agent should comprise at least 5 weight percent of the adhesive composition. The amount of the agent may be at least 8 percent by weight or at least 10 percent by weight. The reinforcing agent may be present in an amount of up to 45 percent by weight, preferably up to 30 percent by weight, more preferably up to 50 percent by weight. Preferably, it may constitute up to 25 weight percent.
[0044] In a preferred embodiment, the PU polymer toughening agent (A) comprises: i) 10 to 95 weight percent ii) from 2 to 60 weight percent hydroxyl-terminated polybutadiene; iii) 2 to 40 weight percent polyisocyanate, iv) 0 to 20 weight percent and v) 0.1 to 50 weight percent of a capping group. These weight percentages are based on the total weight of the reaction mixture.
[0045] The epoxy resins (B) useful in the present invention include a wide variety of curable epoxy compounds and their Useful epoxy resins include liquid, solid and mixtures thereof. Suitable epoxy resins include those described in U.S. Pat. Examples of the above include those described in column 2, line 66 to column 4, line 24 of the specification of No. 4,734,332. Epoxy resins have an average of at least 1.8 epoxide groups per molecule. The epoxy resin is not modified with rubber. The adhesive is not chemically bonded to the rubber prior to curing.
[0046] Typically, the epoxy compound is an epoxy resin, also called a polyepoxide. The polyepoxides useful herein are derived from monomers such as diglycerides of bisphenol A. Diglycidyl ether of bisphenol F, diglycidyl ether of bisphenol F, tetrabromobisphenol Diglycidyl ether of aryl A, novolac-based epoxy resins and tris-epoxy resins higher molecular weight resins (e.g., bisphenol A-based diglycidyl ethers; or unsaturated monoesters polymerized into homopolymers or copolymers. acrylate, glycidyl methacrylate, allyl glycidyl Most preferably, the epoxy compound has an average of at least One pendant or terminal 1,2-epoxy group (i.e., vicinal epoxy group) per molecule Suitable epoxy resins include resorcinol, catechol, hydroquinone, Biphenol, bisphenol A, bisphenol AP (1,1-bis(4-hydroxyphenyl) (triphenyl)-1-phenylethane), bisphenol F, bisphenol K and tetraphenyl Diglycidyl ethers of polyhydric phenol compounds such as methylbiphenol; C2~24 a Diglycidyl ethers of aliphatic glycols such as diglycidyl ethers of alkylene glycols phenol-formaldehyde novolac resin (epoxy novolac resin), Kyl-substituted phenol-formaldehyde resin, phenol-hydroxybenzaldehyde Resin, Cresol-Hydroxybenzaldehyde Resin, Dicyclopentadiene-Phenol Polyglycidyl ethers of phenolic resins and dicyclopentadiene-substituted phenolic resins; and and any combination of any two or more of them. The epoxy resin preferably contains bisphenol A or is preferably mainly bisphenol A. For example, a preferred epoxy resin may be based on diglyceryl ether of bisphenol A. Dow Chemical DER 664 UE solid epoxy is a diethyl ether. do.
[0047] One preferred epoxy resin has the general formula: [ka] (wherein n is typically in the range of 0 to about 25). Basic liquid resins, such as DER331, have a molecular weight in the range of about 180 to 195 g / mol. Others, such as DER332, have an epoxy equivalent weight of about 170-175 g / mol. DER330 can have an epoxy equivalent weight in the range of about 176 to 185 g / mol. The epoxy equivalent weight may range from 100 to 2000 ppm.
[0048] Combinations of epoxy resins can be used to tailor the properties of the epoxy adhesive. In the compositions and methods of the present invention, the epoxy adhesive may contain any amount of epoxy resin. Preferably, the liquid and / or solid epoxy resin comprises 35% by weight of the epoxy adhesive. More preferably, it comprises 40% by weight or more. The epoxy resin should constitute no more than 60% by weight of the epoxy adhesive, and more preferably no more than 55% by weight. do.
[0049] Suitable epoxy resins include, for example, those available from The Dow Chemical Com pany to DER330, DER331, DER332, DER383, DER661 and bisphenol A diglycidyl resins, such as those sold under the name DER662 resin. Ether resins are also included.
[0050] Suitable commercially available epoxy novolac resins include The Dow Chem DEN354, DEN431, DEN438 and DEN4 from ical Company 39 is available for sale.
[0051] Suitable cycloaliphatic epoxy resins include those disclosed in U.S. Pat. Particularly interesting alicyclic olefins include those described in US Pat. No. 3,686,359. The epoxy resin is (3,4-epoxycyclohexyl-methyl)-3,4-epoxy-cyclohexyl. cyclohexane carboxylate, bis-(3,4-epoxycyclohexyl) adipate, Vinylcyclohexene monoxide and mixtures thereof.
[0052] Other suitable epoxy resins include those described in U.S. Pat. No. 5,112,932. Further, examples of oxazolidone-containing compounds include DER592 and DER High performance epoxy-insulators such as those commercially available as 6508 (Dow Chemical) Socyanate copolymers can be used.
[0053] The epoxy resin is preferably a diglycidyl ether of one or more polyhydric phenols or or their mixtures with up to 10 weight percent of another type of epoxy resin. The most preferred epoxy resins are diglycidyl ethers of bisphenol A and bisphenol These are diglycidyl ethers of glycidyl ether of 170 to 600 or more, preferably 225 It may have an average epoxy equivalent weight of ~400.
[0054] Particularly preferred epoxy resins are those having an epoxy equivalent of 170 to 299, particularly 170 to 225. At least one polyhydric phenol having the formula (preferably bisphenol A or bisphenol B) and at least one polyhydric phenol (also preferred). A second diglycidyl ether (of bisphenol A or bisphenol F) having an epoxy equivalent of at least 300, preferably 310 to 600) The ratio of resins is preferably such that the mixture has an average epoxy equivalent of 225 to 400. The mixture may contain up to 20%, preferably up to 10%, of one or more Other epoxy resins may optionally be included.
[0055] The epoxy resin preferably comprises at least about 25 weight percent of the adhesive, more preferably or at least about 30 weight percent, and even more preferably at least 40 weight percent The epoxy resin comprises up to 75 weight percent of the adhesive, more preferably It may constitute up to 60 weight percent.
[0056] In some embodiments, the adhesive composition comprises a bis(phenylene oxide) having an epoxy equivalent weight of up to 225. Sphenol A diglycidyl ether is 30 to 60 weight percent, preferably 40 to 6 0 weight percent, and has an epoxy equivalent of 400 or more, preferably 400 to 1500. Bisphenol A diglycidyl ether having a molecular weight of 0 to 10%, preferably 2 Such adhesive compositions optionally contain up to 6 weight percent of an epoxy novotoxin. Different epoxy resins such as lac resin or epoxy cresol novolac resin are mixed at 0.5 to 1000g / ml. Contains 10 percent by weight.
[0057] The adhesive of the present invention also contains a latent curing agent (C). The curing agent acts as the adhesive as described above. An agent is considered "latent" for purposes of this invention if it exhibits a cure temperature of at least 60°C. The curing temperature is preferably at least 80°C, and more preferably at least 100°C or may be at least 140° C. It may be, for example, as high as 180° C. "Curing temperature" refers to the temperature at which a structural adhesive fully cures within 2 hours and reaches its lap shear strength (DIN This refers to the lowest temperature at which the hardening temperature achieves at least 30% of the hardening point (ISO 1465). The lap shear strength of was measured on samples cured at 180°C for 30 minutes, a condition known as " represents the "fully cured" condition.
[0058] Suitable latent hardeners include boron trichloride / amine and boron trifluoride / amine complexes, Melamine, diallylmelamine, guanamines such as dicyandiamide, methylguanidine , dimethylguanidine, trimethylguanidine, tetramethylguanidine, methylisobutyric acid Guanidine, dimethylisobiguanidine, tetramethylisobiguanidine, heptamethyl Isobiguanidine, hexamethylisobiguanidine, acetoguanamine and benzoguanamine Aminotriazoles, such as 3-amino-1,2,4-triazole, hydrazides For example, adipic acid dihydrazide, stearic acid dihydrazide, isophthalic acid dihydrazide amides, semicarbazides, cyanoacetamides and aromatic polyamines, such as aminodiphenyl Dicyandiamide is an especially preferred curing agent.
[0059] The latent hardener is used in an amount sufficient to harden the adhesive. Typically, the composition Sufficient hardener is provided to consume at least 80% of the epoxide groups present in the article. A large excess beyond that required to consume all of the epoxide groups is usually not necessary. Preferably, the hardener comprises at least about 1 weight percent of the adhesive, more preferably at least about 1 weight percent of the adhesive. Both comprise about 2 weight percent, and even more preferably at least 3 weight percent. The curing agent preferably comprises up to about 15 weight percent of the adhesive composition, more preferably up to about 15 weight percent of the adhesive composition. At most about 10 weight percent, and most preferably at most about 8 weight percent.
[0060] The adhesive of the present invention comprises one or more urea groups and a molecular weight of up to 250 per urea group. The urea compound further comprises at least one urea compound (D) having the structure: [ka] (wherein n is 1 or more, R is unsubstituted or unsubstituted alkyl, cycloalkyl and / or an aromatic radical, R 1 is hydrogen, unsubstituted alkyl, substituted alkyl, phenyl nyl or substituted phenyl, and each R 2are independently alkyl, substituted alkyl, phenyl phenyl or substituted phenyl) R may be a compound obtained by removing an isocyanate group from a mono- or polyisocyanate compound. R can be, for example, a residue of up to 20 carbon atoms or up to 15 carbon atoms. Preferably, R, each R 2 and R 1 (If not hydrogen) is an aliphatic carbon source is bonded to the adjacent nitrogen atom via a nitrogen atom; n is preferably 1 to 4, more preferably is 1, 2 or 3, most preferably 2.
[0061] Examples of aromatic ureas include 3-phenyl-1,-1,1-dimethylurea, 3-(p- 3-(3,4-dichlorophenyl)-1,-1,1-dimethylurea Examples include dimethylphenylureas such as 1,1-dimethylurea.
[0062] Other aromatic ureas include those produced by the reaction of aromatic polyisocyanates with dialkylamines. Examples include 2,4'- and / or 4,4'-methyl 2,4- and / or 2,6-toluene bis(dimethyl urea) Thiol urea).
[0063] Examples of aliphatic ureas include tetramethylurea and tetraethylurea, which are alkyl groups. each independently represents a tetraalkyl group having 1 to 12, preferably 1 to 2, carbon atoms Examples include urea compounds.
[0064] A preferred type of aliphatic urea is a dialkyl urea consisting of an aliphatic (including cycloaliphatic) isocyanate and a dialkyl urea. Examples include isophorone bis(dimethylurea), silylamine, Cyclohexanebis(dimethylurea), Hexane-1,6-bis(dimethylurea), 4,4 '-methylenebis(cyclohexanedimethylurea) and the like. The curing agent is isophorone bis(dimethylurea) under the trade name Omicure U35. Omicure U52 4,4'-methylenebis(phenyldimethylurea) and trade name Omicure U405 phenyldimethylurea, all Emerald Per Formance Materials.
[0065] Preferably, the urea compound comprises at least about 0.1 weight percent of the adhesive, more preferably or at least about 0.5 weight percent, and even more preferably at least 1 weight percent The curing agent preferably comprises up to 5 percent by weight of the adhesive composition, more preferably Preferably it comprises at most 4 weight percent, most preferably at most 3 weight percent .
[0066] The adhesives of the present invention may contain various other optional ingredients in addition to those described above. .
[0067] The adhesive of the present invention may contain one or more fillers (E). These include: (1) the adhesive (2) to reduce the overall cost per unit weight (3) reducing the absorption of moisture or oil from the adhesive or the substrate to which it is applied. and / or (4) promoting cohesive rather than adhesive failure. Examples of suitable mineral fillers include calcium carbonate, calcium oxide, and the like. , talc, carbon black, textile fibers, glass particles or fibers, aramid pulp, boron Fibers, carbon fibers, mineral silicates, mica, powdered quartz, hydrated aluminum oxide, ventona silicic acid, wollastonite, kaolin, fumed silica, silica aerogel, polyurea Examples of the powder include a polyamide compound, a metal powder such as aluminum powder or iron powder, and the like. Other fillers of particular interest are those having an average particle size of up to 200 microns and a maximum particle size of up to 0.2 g. The microballoons have a density of about 25 to 150 mm / cc. The density is preferably about 0.05 to about 0.15 g / cc. A suitable heat-expandable microballoon for this purpose is Dualite Corporation's ion under the Dualite trade name and Akzo Nobel Examples include those sold under the trademark Expancel.
[0068] All or part of the mineral filler has a diameter between 1 and 50 μm (D50, measured by microscope). The fiber may be in the form of a fiber having an aspect ratio of 6 to 20. The fiber diameter is 2 to 2 The thickness may be 0 μm or 2-10 μm, and the aspect ratio may be 8-20 or 8-16. The diameter of a fiber is taken as the diameter of a circle having the same cross-sectional area as the fiber. The aspect ratio of a fiber is , 6 to 25, 6 to 20, 8 to 20, or 8 to 15.
[0069] Alternatively, all or part of the mineral filler may have an aspect ratio of 5 or less and a diameter of up to 100 μm. , preferably in the form of low aspect ratio particles having a longest dimension of up to 25 μm.
[0070] The mineral filler may, for example, be present in an amount of 1 to 40 weight percent of the total weight of the adhesive composition, preferably may comprise 1 to 30 weight percent of the adhesive composition. at least 5 weight percent or at least 7.5 weight percent of the weight of the article, and up to 25 weight percent, up to 20 or up to 15 weight percent of the total weight of the adhesive It may constitute cents.
[0071] The adhesive may be present in an amount of up to 10 weight percent, preferably 1 to 20 weight percent, based on the total weight of the adhesive. It may contain 6 weight percent fumed silica.
[0072] The adhesives of the present invention further comprise one or more additional components (F) common to one-part structural adhesives. For example, the adhesive may include a capped isopropyl alcohol, which is a separate material from the toughening agent described above. The rubber component may include a rubber component that does not include cyanate groups. Such a rubber component is optional. One advantage of the present invention is that even if the adhesive lacks such components, The advantage is that excellent characteristics can be obtained.
[0073] The optional rubber component may have any suitable group, such as, for example, an amino group or, preferably, a carboxyl group. Preferably, the liquid rubber has two or more epoxide reactive groups. Some of the glass is measured at temperatures below -40°C, especially below -50°C, using a differential scanning calorimeter. Transition temperature (T g Such a liquid rubber component preferably contains an epoxy resin and It may be fully or partially reacted to form a rubber-modified epoxy resin having epoxy groups.
[0074] Such liquid rubbers are preferably homopolymers or copolymers of conjugated dienes, In particular, diene / nitrile copolymers. The conjugated diene rubber is preferably a butadiene rubber. or isoprene, with butadiene being particularly preferred.
[0075] Another type of rubber that may be present in the adhesive composition is a core-shell rubber. The shell rubber is a particulate material having a rubbery core. The rubbery core is preferably made of: T less than 20° C., more preferably less than −50° C., even more preferably less than −70° C. g Have The rubber core T g can be much colder than -100°C. The material preferably has a T g Also has at least one shell portion having The core of the core-shell rubber is made of a conjugated diene such as butadiene or n-butyl-, lower alkyl acrylates such as ethyl-, isobutyl- or 2-ethylhexyl acrylate; The polymer or copolymer may be a related polymer or copolymer, or may be a silicone rubber. The shell polymer, which is optionally chemically grafted or crosslinked to the rubber core, is preferably , methyl methacrylate, ethyl methacrylate, or t-butyl methacrylate At least one lower alkyl methacrylate is polymerized. Such methacrylates Homopolymers of the monomers can be used. In addition, up to 40% by weight of the shell polymer can be used. The monomers are styrene, vinyl acetate, vinyl chloride, methyl acrylate, and ethyl acrylate. , butyl acrylate, and the like. The molecular weight of the grafted shell polymer is generally 20,000 to 500,000. Examples of useful core-shell rubbers include those disclosed in European Patent Application Publication No. 1 632 533 A 1 and Kaneka Kane Ace (Kaneka Kane Ace MX 156 and Kaneka Kane Ace MX 120 Contains core-shell rubber dispersion) by Kaneka Corporation These include items that are on sale.
[0076] The total rubber content of the adhesive of the present invention is only 0 weight percent based on the total weight of the adherend. The range can be as high as 30 weight percent. The preferred rubber content is at most 20 weight percent, at most 15 weight percent or at most No portion of the elastomeric toughening agent should exceed the total rubber content by more than 5 percent by weight. This is not taken into account in the calculation.
[0077] In a particular embodiment, the adhesive of the present invention comprises no more than 5% by weight, preferably no more than 1% by weight, More preferably, the adhesive has a total rubber content of 0.5% by weight or less. It could be.
[0078] Additional optional components include monomeric or olefinic compounds optionally present in the adhesive composition. It is an oligomeric, addition-polymerizable ethylenically unsaturated material. This material may be, for example, an acrylate or methacrylate. Compounds, unsaturated polyester, vinyl ester resin or unsaturated polyester resin epoxy To provide a source of free radicals for polymerizing this material, Radical initiators may also be included in the adhesive composition. The inclusion of unsaturated materials allows for in-situ curing of the adhesive by selective polymerization of ethylenic unsaturation. The possibility of bringing about is provided.
[0079] The adhesive composition comprises a dimerized fatty acid, a diluent, a plasticizer, an extender, a pigment and a dye, a flame retardant, Other additives such as thixotropic agents, foaming agents, flow control agents, adhesion promoters and antioxidants. Suitable blowing agents include those of the physical and chemical types. Both agents are included. The adhesive is described in WO 2005 / 118734. As described in, for example, a thermoplastic such as polyvinyl butyral or polyester polyol. It may also contain plastic powder.
[0080] The aforementioned adhesive composition is layered at the bond line between two substrates to form an assembly. The adhesive layer is then cured at the bondline to form an adhesive bond between the two substrates.
[0081] The adhesive can be applied to the substrate by any convenient technique. Depending on the application, it can be applied cold or warm. Manually and / or robotically using a King Gun, other extrusion device or jet spray method Once the adhesive composition has been applied to at least one surface of the substrate, The substrates are contacted such that the adhesive is located at the bond line between the substrates.
[0082] After application, the adhesive is cured by heating it above its cure temperature. The heating temperature is at least 60°C, preferably 80°C or higher, and more preferably 140°C or higher. Preferably, the temperature is less than or equal to 180°C.
[0083] The adhesives of the present invention are suitable for use on wood, metal, coated metal, aluminum, various plastics and Used to bond a variety of substrates together, including filled plastic substrates, fiberglass, etc. In one preferred embodiment, the adhesive is used to bond automotive parts together. These parts are used to attach components to automobiles or to join automobile parts to automobiles. Steel, Coated Steel, Galvanized Steel, Aluminum, Coated Aluminum The materials can be cellulose, plastic and filled plastic substrates.
[0084] Applications of particular interest include the connection of automotive frame components to each other or to other components. Frame components are often made of cold rolled steel, galvanized metal or aluminum. These metals are often contaminated with the oils mentioned above. The components to be joined may be metal as just described, or may be made of other metals, plastics, or other materials. The material may be a composite material, etc.
[0085] Assembled automobile frame components are typically coated with coating materials that require bake hardening. The coating is typically applied at temperatures ranging from 140°C to over 200°C. In such cases, the frame components are baked at temperatures that are Apply adhesive to the product (which may be oil-coated as described above) and After that, a coating is applied, and the adhesive is cured at the same time as the coating is baked and cured. It is often convenient to apply the adhesive and the coating. During this time, the assembly is held in place until the curing step is performed, with the substrate and adhesive held against each other. The mechanical means may be used as a fastening device. These can be used, for example, as a protective layer that can be removed after the curing step is complete. These include temporary mechanical means such as various types of clamps, bands, etc. Mechanical fastening means such as various types of welds, rivets, screws and / or crimping methods provide a permanent connection. Alternatively or additionally, a final curing step may be performed after the coating is applied. One or more specific portions of the adhesive composition are cured while the remainder of the adhesive remains uncured until the adhesive is applied. By spot curing parts to form one or more localized adhesive bonds between the substrates. Fixation can be performed by EXAMPLES
[0086] The following examples are offered to illustrate the present invention but are not intended to limit its scope. All parts and percentages are by weight unless otherwise indicated. Unless otherwise indicated, all molecular weights are number average.
[0087] Table 1 shows the raw materials used in Reinforcement Examples 1-5.
[0088] [Table 1]
[0089] Synthesis of reinforcers. The toughening agent may be prepared by a three-stage process or a two-stage process as described hereinafter. Unless otherwise specified, the amounts of components [a]-[g] are in weight percent.
[0090] Two-step process: 1. First reaction step: Components [a] and [b] are placed in a lab reactor and heated to 120°C. The mixture is mixed under vacuum at 120°C for 30 minutes and then cooled to 60°C. When the mixture reaches 60°C, add component [c] and mix. After 2 minutes, add component [g]. is added and the mixture is reacted under nitrogen at 85° C. (bath temperature) for 45 minutes. 2. Second reaction step: Components [e] and [f] are added to the mixture obtained in the first step; The mixture is stirred under nitrogen at 95° C. (bath temperature) for 90 minutes. Finally, the mixture is placed under vacuum. The mixture is stirred at 95°C for 10 minutes to degas the mixture.
[0091] Three-step process: 1. First reaction step: Components [a] and [b] are placed in a lab reactor and heated to 120°C. The mixture is mixed under vacuum at 120°C for 30 minutes and then cooled to 60°C. When the mixture reaches 60°C, add component [c] and mix, then after 2 minutes, add component [g]. Add and react the mixture at 85° C. (bath temperature) under nitrogen for 45 minutes. 2. Second reaction step: Component [e] is added to the mixture obtained in the first step, and the mixture is nitrogenated. Stir under vacuum at 95°C (bath temperature) for 60 minutes. 3. Third reaction step: Component [f] is added to the mixture obtained in the second step, and the mixture is nitrogenated. Stir under vacuum at 95°C (bath temperature) for 90 minutes. Finally, the mixture is cooled to 95°C under vacuum. Stir and degas at 37°C for 10 minutes.
[0092] The compositions of reinforcement examples 1 to 5 are shown in Table 2.
[0093] [Table 2]
[0094] Table 3 shows the raw materials used in epoxy adhesive composition Examples 6-20.
[0095] [Table 3]
[0096] Adhesive composition examples 6-20 are summarized in Table 4. Examples 6-9 and 11 are The only difference is the composition of the toughening agent. The hydrophobicity of the toughening agent and adhesive formulation is 8>11>7>6> 9. Examples 10-13 are the same except for the amount of accelerator. The amount of accelerator decreases from 10 to 13. Examples 14-16 and 17-19 are Only the composition and amount of accelerator differs. Examples 10-16 contain urea type accelerators, while , Examples 17-19 include a Mannich base type accelerator.
[0097] The following rheological, thermal and physical properties were measured for adhesive composition examples 6 to 20. were determined and the results are reported in Table 5: "GPC method" system: Malvern: Viscotek GPCmax / Visc otek TDA; Column: Mixed-D precolumn, then Agilent Mi xed-D 300*7.5 Multi-detection system (Viscotek TDA): RI, Viscosity, RALS, LALS; Eluent: THF; Flow rate: 1.0ml / min; Standard: PS; Calculation : Absolute molecular weight (Universal Calibration: H. Benoit, J. Polym.Sci.B,5(1967),pp.753-759), "Rheology": Bohlin CS-50 rheometer, C / P20, rise / fall Rotational viscosity and yield stress determined using 0.1-20s / 1, Casson model Evaluated according to Dell; "DSC" Differential Scanning Calorimetry is performed by Mettler with Star Software Toledo DSC 821, 25°C to 250°C, 10° / min ramp Determined in; "Lap shear strength" according to DIN EN 1465 at a test speed of 10 mm / min:1 The failure mode was determined using a bond area of 0.0×25 mm and an adhesive layer thickness of 0.3 mm. , with a failure rate of 0 to 100 (100% being complete failure) as CF (cohesive failure) or AF ( reported as adhesive failure; "Impact peel strength" is measured according to ISO11343 at a test speed of 2m / s: 20x30mm of bond area, determined using an adhesive layer thickness of 0.3 mm; The "tensile properties" of tensile strength, elongation and elastic modulus were measured using a test speed of 10 mm / min. Determined in accordance with DIN EN ISO 527-1.
[0098] Mechanical tests were carried out on hot-dip galvanized steel 420 supplied by Voest Alpine. LAD+Z100MB (thickness 1.2mm) and electrolytic zinc-plated steel: HC300LAD+Z The test was carried out using a steel test piece of E75-75 (thickness 1.0 mm).
[0099] The humidity exposure test is carried out by applying the adhesive composition according to the DIN procedure and the specified bond area dimensions. The test is carried out using lap shear specimens by preheating the specimens at 170°C for 6 minutes. The specimens are then pre-cured and subsequently exposed to 40°C and 98% relative humidity for 5 weeks. Condition at 50% relative humidity for at least 1 hour and then oven at 175°C for 25 minutes. Final cure is performed in . The test results are reported.
[0100] 1 to 3 show the results of Example 12 (10%), Example 6 (40%) and Example 20, respectively. Photographs of lap shear specimens with 100% (100%) adhesive failure are shown.
[0101] [Table 4]
[0102]
Table 5
Claims
1. A) a blocked PU polymer toughening compound; B) an epoxy resin component comprising a solid epoxy resin, a liquid epoxy resin, or a mixture thereof; ; C) a curing agent; D) urea compounds; and E) Optionally, a filler A one-component structural adhesive comprising the blocked PU polymer toughening agent (A): i) polyethers, ii) hydroxyl-terminated polybutadiene; iii) polyisocyanates, iv) a chain extender, and v) Capping Group 1. A one-part structural adhesive that is the reaction product of a reaction mixture comprising:
2. The polyether (A)(i) is a polytetrahydrofuran-diol polymer. The one-component structural adhesive of claim 1 .
3. The polyisocyanate (A)(iii) is 1,6-hexamethylene diisocyanate. The one-component structural adhesive of claim 1 .
4. The capping group (A)(iv) is cashew nut shell liquid oil. A one-component structural adhesive.
5. formula: 【Chemistry 1】 The one-component structural adhesive of claim 1 , comprising an epoxy resin (B) having the formula:
6. The one-component composition according to claim 1, wherein the urea compound (D) is phenyldimethylurea. Construction adhesive.
7. The filler (E) is selected from the group consisting of fumed silica, calcium carbonate, calcium oxide, and wola.
2. The method of claim 1, wherein the inorganic filler is one or more of stonite, talc, glass beads, and hollow glass spheres. A one-component structural adhesive.
8. A) 5 to 25 weight percent of said blocked PU polymer toughener compound; B) 1 to 10 weight percent of a solid epoxy resin and 30 to 60 weight percent of a liquid the epoxy resin component comprising an epoxy resin; C) 1 to 8 weight percent of said curing agent; D) 0.1 to 3 weight percent of said urea compound; and E) 0 to 30 weight percent of said filler. and the weight percentage is based on the total weight of the one-part structural adhesive. The one-component structural adhesive according to claim 1.
9. The blocked PU polymer toughening agent (A) reaction mixture is i) 10 to 95 weight percent of said polyether; ii) 2 to 60 weight percent of said hydroxyl-terminated polybutadiene; iii) 2 to 40 weight percent of said polyisocyanate; iv) 0 to 20 weight percent of said chain extender, and v) 0.1 to 50 weight percent of said capping group.
2. The method of claim 1 , wherein the weight percentages are based on the total weight of the reaction mixture. One-component structural adhesive.
Citation Information
Patent Citations
One-part, toughened epoxy adhesive with improved adhesion to oily surfaces and high wash-off resistance
JP2018530642A
Blocked Polyurethane Reinforcing Agent for Epoxy Adhesives
JP2018532820A
High temperature epoxy adhesive formulations
WO2018236454A1
Adhesive composition
WO2019079026A1